Changes in Women’s Social Roles and Functions in Gender Dichotomy Resistance - Khairullah Khairullah (PERSPEKTIF, 2022)
This research aims to strengthen the form of resistance to the implementation of gender-based discrimination among women. The theory used in this study is the structural theory of conflict to portray the existing problems. The study methodology chosen is qualitative, with data collection techniques such as interview, non-participatory observation, and literature studies.The subject of the informant in this research is a 1st Semester student Communication Studies, Medan Area University Academic Year 2021/2022, who took Social Theories in Class A2.The results and discussion of this study indicate that the changing roles and social functions of women in the era of emancipation, in fact have not resolved various forms of injustice based on gender, especially in the form of objectification. Be it is in the family domestic sector or the public, such as : politic, economic, social, culture, education and job. Therefore, this research recommends that all level of society must be aware and gender sensitive. Thus, women are no longer a subordinate class in society, and they can give their best contribution to the nation and state. In addition to the prevailing consensus structural rules in the form of values, norms, or laws should not be gender biased. In the end, women must have the courage to fight with a dynamic and heterogeneous attitude in facing the turmoil of the times. Man and woman are equal, and must respect each other!